Sinema Independen di Yogyakarta 1999-2008: Idealisme di Tengah Krisis Infrastruktur - Mr Masduki (Program Studi Ilmu Komunikasi, 2010)
The growing up of Indonesian cinema in the period 0/1999-2008 was indicated by the development of creative works and community based alternative cinemas or indie movie. Used a qualitative-descriptive method, writer done a small-research in Yogyakarta around April-September 2009 and found some interesting trends. Yogyakarta has become a very dynamic city in Indonesia in term of independent cinema communities. This research also found three connecting areas that support above situation. First, the actively independent communities in the field of university students and non-university students. Second, the openness of alternative bioscope or cinema room such us Kinoki and Yogyakarta based French Cultural Center. Third, some local and regional film festivals held in Yogyakarta that regularly exhibit independent cinema works. The majority of independent cinema production and communities driven by higher attention to cinema as a popular medium for free expression and critical concern to the current social and political situation. The limitation of infrastructure, regulation protected and public support are some obstacles need to be solved in the future.